Scabies Prevalence on Cats and Rabbits in Animal Hospital of East Java Livestock Service on 2021 - Ramadhanty, Miladhiyah Nabila; Kusnoto, Kusnoto; Hastutiek, Poedji; Mufasirin, Mufasirin; Setiawan, Boedi; Hestianah, Eka Pramyrtha (Journal of Parasite Science, 2024)
This study aims to obtain information and data on the prevalence of scabies in cats and rabbits at the Animal Hospital of East Java Livestock Service Surabaya. The data obtained in this study are data on visitors or pet owners to the Animal Hospital in January - December 2021. The type of research is descriptive research. The data obtained tabulated and analyzed with a prevalence test and discussed descriptively. The prevalence of scabies in cats and rabbits at the study was 5.62% or 76 positive of 1352 visiting clients. Forty five of them were cats (59.21% of 76) and 31 were rabbits (40.79% of 76). Scabies attacks animals in the nose, mouth and ears. Scabies also causes weight loss, hair loss, irritation, anemia and even death. Scabies treatment at the research location is by cleaning the scars caused by scabies, applying an ointment containing 5% permethrin, and giving anti-histamine and anti-parasitic as well as providing supportive therapy in the form of grooming using shampoo containing anti-ectoparasites. Pet owners are expected to follow the advice given by animal hospital staff who have provided knowledge in terms of controlling and preventing Scabies.